Risk factors for in-hospital mortality in SARS-CoV-2 pneumonia adult patients from Lima, Peru - Rodriguez-Zuniga, Milton J. M. (2020)
Objective: this study aimed to describe the main factors associated to mortality in a cohort of patients hospitalized with SARS-CoV-2 pneumonia in a public hospital in Lima, Peru. Materials and methods: this was a retrospective cohort study, with a non-random convenience sampling. Adult patients with confirmed/suspicious SARS-CoV-2 pneumonia with rapid and/or molecular tests were included. Demographic, clinical, laboratory, tomographic and treatment variables were identified. Descriptive statistics, bivariate analysis, and Poisson regression techniques were used to determine the adjusted relative risk (aRR). Results: 122 patients were included, 70.5% were male, with a mean age of 55.8 years, with a history of obesity (25.4%) and high blood pressure (HBP, 13.1%). The multivariate analysis of clinical factors identified that age (aRR 1.03; 95% CI: 1,00-1.06; p=0.021), body mass index (BMI; aRR 1.03; 95% CI: 1.01-1.05; p=0.006), HBP (aRR 1.68; 95% CI: 1.09-2.56; p=0.017), PaO2/FiO2 index (aRR 0.99; 95% CI: 0.99-1.00; p<0.001), exposure to lopinavir/ritonavir (LPV/r; aRR 0.83; 95% CI: 0.76-0.91; p <0.001), and systemic corticosteroids (aRR 1.18; 95% CI: 1.09-1.27; p<0.001) were significantly associated with mortality. Conclusions: Age, BMI, HBP, PaO2/FiO2 index, and exposure to corticosteroids and LPV/r were associated with mortality in our cohort of patients hospitalized with SARS-CoV-2 pneumonia.